Continuum of Care for Diabetes and Hypertension Patients During the Pandemic Era: Bridging the Gap - Widyaningrum, Kurnia; Zuhriyah, Lilik; Wardhani, Viera; Rudijanto, Achmad (Malaysian Journal of Medical Sciences, 2025)
Background: Diabetes mellitus (DM) and hypertension (HT) are chronic diseases with an increasing prevalence in Indonesia. Continuum of care (CoC) offers a crucial management strategy, yet its implementation has faced challenges, particularly during the COVID-19 pandemic. This study examines how the Health Belief Model (HBM) construct intersects with CoC implementation in primary healthcare (PHC) settings under pandemic conditions, addressing a critical gap in understanding chronic disease management adaptations.Methods: A cross-sectional study, involving 351 DM or HT patients at nine PHC centres, was conducted between February and April 2021. Data collection included HBM-based questionnaires and structured patient surveys, analysed through descriptive statistics and path analysis.Results: Respondents were predominantly women (55.0%) aged 41–60 years old (48.1%), and with secondary or higher education (74.6%). A total of 43% reported self-medicating during the pandemic, reflecting behavioural shifts in care-seeking. Path analysis showed age consistently influenced all five HBM perceptions, while education was associated with three: perceived susceptibility, severity and benefit. Perceived benefit was the strongest positive predictor of revisit behaviour (β = 0.264; P = 0.019), whereas perceived severity had a negative effect (β = –0.146; P = 0.024). Indirectly, age and education influenced revisit behaviour through perceived benefit and susceptibility, which were the most consistent mediators.Conclusion: This study demonstrates the utility of HBM in understanding CoC adherence during health crises. The findings support the tailoring of chronic disease strategies by age and education, and enhancing CoC with digital technologies and expanded Prolanis programmes. Future research should assess the long-term impacts of HBM-based interventions on adherence and outcomes.